Faktor-Faktor Yang Berhubungan Partisipasi Ibu Balita Dalam Kegiatan Posyandu Balita Di Batalion Yonif Raider 112/Dj Banda Aceh Tahun 2023 - Aris Winandar; Muhammad Darimi; Gunawan Gunawan (Serambi Saintia : Jurnal Sains dan Aplikasi, 2023)
The lack of participation of mothers in bringing their toddlers to Posyandu at Battalion Yonif Raider 112/Dj Banda Aceh has different reasons. mothers who have children under five with a total sampling technique. The instrument used was a questionnaire on the intervention factor of the commander and the husband's role as well as observation with anthropometry measuring weight, height according to the age of the toddler using the Z score table. The results obtained showed a relationship between the commander's intervention and the participation of the mother with a p-value of 0.043, and no there is a r elationship between husband's support and mother's participation in toddler posyandu activities with a p-value of 0.199 and there is no relationship between nutritional status and mother's participation in toddler posyandu activities with a p-value of 0.372 in Yonif Raider Battalion 112/Dj Banda Aceh in 2023. Thus expected for cadres to be able to increase the coverage of posyandu by way of door to door to be able to provide quality posyandu programsKeywords: Intervention, husband's role, nutritional status